2017
DOI: 10.1016/s1470-2045(17)30194-8
|View full text |Cite|
|
Sign up to set email alerts
|

European Association for Neuro-Oncology (EANO) guideline on the diagnosis and treatment of adult astrocytic and oligodendroglial gliomas

Abstract: Association for NeuroOncology (EANO) (2017). European Association for Neuro-Oncology (EANO) guideline on the diagnosis and treatment of adult astrocytic and oligodendroglial gliomas. Lancet Oncology, 18(6):e315-e329. DOI: https://doi.org/10.1016/ S1470-2045(17) Implementing this guideline requires multidisciplinary and multiprofessional structures of care and defined processes of diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
708
1
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 915 publications
(728 citation statements)
references
References 82 publications
5
708
1
14
Order By: Relevance
“…Current median survival time for patients with oligodendrogliomas WHO grade III is 12-14 years, and longer for patients with oligodendroglioma WHO grade II [2]. Primary treatment is maximal safe resection, followed by radiotherapy and chemotherapy for highrisk patients [4,5]. Based on their chemosensitivity, it has recently been suggested that chemotherapy may be the optimal primary treatment for oligodendrogliomas [6].…”
Section: Introductionmentioning
confidence: 99%
“…Current median survival time for patients with oligodendrogliomas WHO grade III is 12-14 years, and longer for patients with oligodendroglioma WHO grade II [2]. Primary treatment is maximal safe resection, followed by radiotherapy and chemotherapy for highrisk patients [4,5]. Based on their chemosensitivity, it has recently been suggested that chemotherapy may be the optimal primary treatment for oligodendrogliomas [6].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In a study by Kaloshi et al from 2009, 8% of LGG diagnosed from 1997 and onwards occurred in patients 60 years or older. 9 For example, a more active surgical management for LGG is advocated nowadays, in contrast to earlier practice when potential undertreatment may have occurred. The overall survival in older patients was significantly impaired, which seemed related to an accumulation of negative prognostic factors in elderly patients and perhaps also due to undertreatment.…”
mentioning
confidence: 99%
“…Despite the use of aggressive therapies, such as surgery, radiation therapy, chemotherapy, and anti‐angiogenic therapy, prognosis of gliomas remains poor . More importantly, therapeutic strategies vary among different grades, as well as different subtypes of glioma . Therefore, accurate determination of glioma grade and subtype needs to be addressed.…”
mentioning
confidence: 99%